2014
DOI: 10.1071/ah14059
|View full text |Cite
|
Sign up to set email alerts
|

Predicting unplanned readmission after myocardial infarction from routinely collected administrative hospital data

Abstract: Objective. Readmission rates are high following acute myocardial infarction (AMI), but risk stratification has proved difficult because known risk factors are only weakly predictive. In the present study, we applied hospital data to identify the risk of unplanned admission following AMI hospitalisations.Methods. The study included 1660 consecutive AMI admissions. Predictive models were derived from 1107 randomly selected records and tested on the remaining 553 records. The electronic medical record (EMR) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Overall, 56 of the 60 included studies reported model discriminative ability (C-statistic), ranging from 0.21 46 to 0.88. 63 The area under curve for validation studies ranged from 0.53 30 to 0.83, 63 being slightly lower than those for the derivation study, 0.21 46 to 0.88. 63 For all-cause unplanned hospital readmission models, the C-statistic was reported by 14 studies ranging from 0.55 13 to 0.80.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Overall, 56 of the 60 included studies reported model discriminative ability (C-statistic), ranging from 0.21 46 to 0.88. 63 The area under curve for validation studies ranged from 0.53 30 to 0.83, 63 being slightly lower than those for the derivation study, 0.21 46 to 0.88. 63 For all-cause unplanned hospital readmission models, the C-statistic was reported by 14 studies ranging from 0.55 13 to 0.80.…”
Section: Resultsmentioning
confidence: 73%
“…Of those, only nine developed models had a C-statistic value >0.70. 30 32 34 35 38 40 41 49 50 In particular, 13 of the 17 models (12 developed and 5 existing) from 11 studies with the special focus on heart failure-related readmissions were presented with C-statistic <0.70. 39 40 42ā€“48 For surgical-related readmissions (6 studies), the C-statistic ranged from 0.59 67 to 0.85 69 among 7 developed models.…”
Section: Resultsmentioning
confidence: 99%
“…The median overall observed all-cause 30-day readmission rate across studies was 16.3% (range 10.6ā€“21.0%). The objective of most studies (n=7) was to develop models to identify patients hospitalized for myocardial infarction at high risk for readmission for potential intervention, 19ā€“22, 24, 27, 29 while the objective of three studies of the CMS AMI administrative model was to estimate hospital-level risk-adjusted 30-day readmission rates for hospital profiling. 23, 25, 26 One study focused on identifying patient- versus hospital-level predictors for cardiac disease-related readmission.…”
Section: Resultsmentioning
confidence: 99%
“…23, 25, 26 One study focused on identifying patient- versus hospital-level predictors for cardiac disease-related readmission. 28 All studies were conducted in the U.S. except for Rana et al, 27, 28 which was conducted at a single community medical center in Australia, and Rodriguez-Padial et al, conducted in Spain using administrative data from the Spanish National Health System.…”
Section: Resultsmentioning
confidence: 99%
“…These results correspond with previous studies using EHR data to develop risk models, illustrating that EHR-based models perform better with nearer-term events. [14][15][16][17][18][19][20][21] Moreover, when comparing the "important" variables over different time horizons, previous work has similarly suggested that more "dynamic" metrics are important for nearer-term outcomes and more "stable" metrics are important for longer-term events. 17 This finding stresses the importance of machine-learning methods capable of handling large numbers of disparate predictor variables.…”
Section: Discussionmentioning
confidence: 99%